DEVELOPMENT OF SOCIO-CULTURAL LIFE AND PEDAGOGICAL THOUGHT IN THE BUKHARA KHANATE DURING THE FIRST HALF OF THE 16TH CENTURY (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article highlights the significant contributions of one of the prominent Shaybanid rulers, Abdullah Khan II, to the development of science, art, culture, education, and other fields during the 16th century in the Bukhara Khanate. It also discusses notable scholars, poets, artists, calligraphers, teachers (mudarris), and other representatives of science and culture from that era, along with their works and valuable insights into the socio-cultural environment of the time.